Faculty Senate, Minutes, May 17, 2007 - Faculty Senate, Valdosta State University (Valdosta, Ga: Valdosta State University Archives and Special Collections, 2007)
Valdosta State University. Faculty Senate, Minutes, May 17, 2007. Chairperson, Ronald M. Zaccari; Vice Chairperson, Louis Levy; Executive Secretary, Christine James; Parliamentarian, Richard Haptonstall;
1 electronic document. Faculty Senate, Minutes, May 17, 2007. 118 pages. 952,230 bytes.
Keywords: Valdosta State University. Faculty Senate; Minutes (Records); Committees; Electronic records